The development of new substances in the first half of the 20th century: the case of Thomas Midgley, Jr. - Viana, Hélio Elael Bonini; Porto, Paulo Alves (Circumscribere International Journal for the History of Science, 2012)
In the first decades of the 20th century, the chemical industry developed many new substances in response to technological demands. Produced on a large scale, these new chemicals were released into the environment, leading to some undesirable consequences. This paper presents the case of Thomas Midgley, Jr. (1889 – 1944), recognized as one of the greatest industrial chemists of his time for having solved two major technological problems: the improvement of gasoline quality, by developing tetraethyl lead as an antiknock additive; and the development of chlorofluorocarbons (CFCs) as fluids for refrigerators. The study of Midgley’s trajectory shows how this mechanical engineer changed his research strategies from trial and error to the use the periodic table of elements as a guide. This case also suggests reflections on the different dimensions of risk are intrinsic to chemical activity.